Species of the genus Aragara Walker (Diptera: Chloropidae: Chloropinae: Mindini) from China with key to species of the world - Liu, Xiaoyan; Yang, Ding (Zootaxa, 2014)
The genus Aragara Walker is newly recorded from China. The following two species are described new to science: A. flavaristata sp. nov. and A. menglaensis sp. nov. One species, A. trilineata Cherian, is newly recorded from China, and one new combination, A. sinensis (Yang & Yang), is proposed. A key to world species of genus Aragara is given.